1992
DOI: 10.1021/bi00164a003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of monoclonal antibodies against voltage-dependent potassium channels raised using .alpha.-dendrotoxin acceptors purified from bovine brain

Abstract: Seven monoclonal antibodies raised against alpha-dendrotoxin-sensitive K+ channels, purified from bovine cerebral cortex, recognize these proteins in their native or denatured states, via interaction with the alpha- but not the beta-subunit. This finding, together with a similar observation made with polyclonal antibodies, shows that the latter is a distinct protein and not a proteolytic fragment of the larger subunit. Also, coimmunoprecipitation of alpha- and beta-subunits provides further evidence that both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 38 publications
2
27
0
Order By: Relevance
“…3A). This yielded a pattern similar to that obtained by silver staining except that an additional band (-56 kDa) was visible; an equivalent minor protein was also detected by autoradiographic analysis of 125I-labeled acceptor (5). The latter may be the bovine equivalent of Kv (28).…”
supporting
confidence: 72%
See 1 more Smart Citation
“…3A). This yielded a pattern similar to that obtained by silver staining except that an additional band (-56 kDa) was visible; an equivalent minor protein was also detected by autoradiographic analysis of 125I-labeled acceptor (5). The latter may be the bovine equivalent of Kv (28).…”
supporting
confidence: 72%
“…Voltage-sensitive Ca2+ and Na+ channels possess one a subunit of -200 kDa consisting of four repeat domains (2,3). On the other hand, the isolated neuronal K+ channels (see below) contain four a subunits (4); the predominant one has an apparent molecular mass of =78 kDa but different sized minor variants are also present (5). It is well documented that the properties of expressed currents are strongly influenced by 1 subunits in the case of Na+ (6) or by 13, 'y, and a2/8 subunits for Ca2+ channels (2,7,8).…”
mentioning
confidence: 99%
“…Immunoprecipitation of K+ channel complexes from radioiodinated rat brain membranes using antibodies specific for the Kv2.1 K+ channel o-subunit (nomenclature according to Chandy, 1991) revealed the presence of a 38 kDa P-subunit polypeptide in tight association with this delayed rectifier K+ channel complex (Trimmer, 1991). Similarly, affinity purification and immunoprecipitation of the oc-dendrotoxin (DTX) sensitive K+ channel complex from bovine brain revealed, in addition to o-subunit polypeptides, the presence of 38 kDa and 41 kDa P-subunit polypeptides in association with the DTX acceptor complex (Parcej and Dolly, 1989;Scott et al, 1990;Muniz et al, 1992). A cDNA encoding a DTX acceptor P-subunit was recently isolated from bovine brain by Scott et al (1994b).…”
mentioning
confidence: 98%
“…22 This would suggest that the remaining heterogeneity may be due to post-translational modification of the protein. Previously we have shown that Kv1.2 examined in brain membranes 23 exhibited similar behaviour during SDS-PAGE, due partly to N-glycosylation. It has been shown that Kv1.2 and other channels are additionally modified by tyrosine 24 and serine/threonine phosphorylation.…”
Section: Resultsmentioning
confidence: 72%
“…63 -65 Other methods SDS-PAGE and Western blotting were carried out as described. 23 Rat brain cerebrocortical synaptosomal membranes were prepared as described. 35 …”
Section: Two-dimensional Crystallisationmentioning
confidence: 99%